A qualitative study to defıne, knowledge, attitudes and practices of about vaginal discharge [Vajinal akıntı hakkındaki bilgi, tutum ve davranışları saptamaya yönelik niteliksel bir c ̧alışma] - KARAVUŞ, MELDA (Gulhane Military Medical Academy, 2012)
AIM: The purpose of this qualitative study; to defi{dotless}ne, knowledge, attitudes and practices of women about vaginal discharge and vaginal douche which is a factor related to the discharge. METHOD: The research has been performed in Umraniye district of Istanbul with women between ages 23- 65 who have been married at least once. Eleven focus group discussions has been established and interviewed with 63 women. İnterviews had been recorded with audio recording devices after receiving permission of the participants, then all the records had been figured out and analyzed in Excel software. RESULTS: Most of the women had stated that they could distinguish the vaginal discharge. Besides the ones that consult to the health institutes and doctors about the problems related with the vaginal discharge, considerable proportion of participants had stated that they were referring to the using traditional methods. In a period of time, most of them had applied or were still applying the vaginal douche which is a factor related to the vaginal discharge. CONCLUSION: Mostly the usage of herbal products and hot practises had been defined as traditional methods for eliminating the abnormal discharge. The reason of vaginal douche application had been declared as cleanliness, religious belief and contraception.
Keywords: Contraception; Discharge; Qualitative research; Vagina; Vaginal douche